2013
DOI: 10.4236/jdm.2013.34036
|View full text |Cite
|
Sign up to set email alerts
|

The association of depression and perceived stress with beta cell function between African and Haitian Americans with and without type 2 diabetes

Abstract: Background: Diabetes and diabetes-related complications are major causes of morbidity and mortality in the United States. Depressive symptoms and perceived stress have been identified as possible risk factors for beta cell dysfunction and diabetes. The purpose of this study was to assess associations between depression symptoms and perceived stress with beta cell function between African and Haitian Americans with and without type 2 diabetes. Participants and Methods: Informed consent and data were available… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Comparably, Huffman and associates [ 24 ] identified that African Caribbeans with type 2 diabetes had a depression score 3.2 points higher than those without type 2 diabetes. de Caluwé et al showed diabetes prevalence to be 7.6% higher in patients with significant mental illness than in the general population [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Comparably, Huffman and associates [ 24 ] identified that African Caribbeans with type 2 diabetes had a depression score 3.2 points higher than those without type 2 diabetes. de Caluwé et al showed diabetes prevalence to be 7.6% higher in patients with significant mental illness than in the general population [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Three synthesized themes were identified: (1) prevalence of comorbid mental health problems and chronic NCDs ( n = 10); [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]; (2) factors that mitigate or mediate the association between mental health problems and chronic NCDs ( n = 11) [ 23 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 ]; —(2a) factors influencing self-management ( n = 4); [ 26 , 27 , 29 , 30 ]; (2b) association between mental health and NCD outcomes—studies focused on (2b1) risk factors ( n = 9) [ 23 , 24 , 25 , 26 , 27 , 28 , 31 , 32 , 33 ]; and (2b2) protective factors ( n = 3); [ 24 , 31 , 33 ]; and (3) varied results ( n = 3) [ 27 , 28 , 29 ]. The results are summarized in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations